1999
DOI: 10.1128/mcb.19.12.8263
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Substrate-Specific Requirement of the Splicing Factor U2AF35 and for Its Function after Polypyrimidine Tract Recognition by U2AF65

Abstract: 35 and a novel function for this factor in pre-mRNA splicing.The first ATP-dependent step in the assembly of splicing complexes is the stable association of U2 snRNP with the 3Ј part of the intron (reviewed in reference 12), which includes the branch point region, the polypyrimidine (Py) tract, and the conserved dinucleotide AG at the 3Ј splice site. The branch point region establishes base-pairing interactions with U2 snRNA that are critical for catalysis of the splicing reaction. The Py tract, particularly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(115 citation statements)
references
References 43 publications
8
106
1
Order By: Relevance
“…It is likely that stronger BP 0 (in terms of U2 snRNA complementarity) can compensate for lower AG affinity to U2AF, leading to the recognition of BP 0 in a U2AF-independent manner (or less dependent than in the case of canonical BP). This model is supported by our U2AF depletion experiments and is consistent with previous findings that BP recognition may depend or not on AG binding to U2AF35, according to BP and 3 0 ss sequence and organization 11,[16][17][18] . In contrast, SF3B1 WT may allow a more promiscuous binding of U2 snRNA to both canonical and alternative BPs, and in this case, the final choice of BP may be determined by context, especially 3 0 ss affinity for U2AF.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It is likely that stronger BP 0 (in terms of U2 snRNA complementarity) can compensate for lower AG affinity to U2AF, leading to the recognition of BP 0 in a U2AF-independent manner (or less dependent than in the case of canonical BP). This model is supported by our U2AF depletion experiments and is consistent with previous findings that BP recognition may depend or not on AG binding to U2AF35, according to BP and 3 0 ss sequence and organization 11,[16][17][18] . In contrast, SF3B1 WT may allow a more promiscuous binding of U2 snRNA to both canonical and alternative BPs, and in this case, the final choice of BP may be determined by context, especially 3 0 ss affinity for U2AF.…”
Section: Discussionsupporting
confidence: 80%
“…15). The low frequency of G nucleotide immediately following alternative AG 0 sites suggests lesser dependence to U2AF1 compared with the canonical AG at the step of 3'ss recognition [16][17][18] . To test this hypothesis, MP41 and HEK293T cells were transiently transfected with siU2AF1 or siU2AF2.…”
Section: Sf3b1 Mutations Promote Upstream Alternative Acceptorsmentioning
confidence: 99%
“…This observation may explain its absence in C. merolae, in which this distance averages 29 nt. In contrast, human Mud2 (U2AF2), which binds the polypyrimidine tract, was found to be critical for excision of all introns tested (57). Because there is no polypyrimidine tract in C. merolae (6), we suggest that CmMud2 could bind the branch site directly, as has been reported in S. cerevisiae (58), which also has less prominent polypyrimidine tracts.…”
Section: Dead Box Proteinsmentioning
confidence: 62%
“…In support of this model, several studies demonstrated increased U2AF LG binding to 3Ј-splice sites in an ESE-dependent manner in nuclear extracts (Wang et al 1995;Zuo and Maniatis 1996;Graveley et al 2001). However, other studies failed to find increased ESE-dependent U2AF cross-linking (Guth et al 1999;Kan and Green 1999;Li and Blencowe 1999), possibly due to different experimental conditions (Guth et al 2001). In one instance, an ESE promoted splicing by counteracting the negative effect of a downstream splicing silencer (Kan and Green 1999;Shen et al 2004a).…”
mentioning
confidence: 75%